Criticism of the Minimal Use of Linguistics as a Solution to Civilization Problems - Siregar, Iskandarsyah (BIRCU, 2025)
This article critically examines the marginal role of linguistics in addressing global civilizational challenges, despite the discipline’s capacity to interpret, deconstruct, and reshape human understanding across domains such as politics, culture, education, health, and the environment. Through a qualitative methodology grounded in critical discourse analysis, the study investigates why linguistic science remains underutilized in interdisciplinary strategies aimed at solving complex societal problems. Findings reveal three interrelated factors: institutional marginalization of linguistic expertise in policy design, persistent positivist biases that favor quantitative disciplines over interpretive ones, and widespread public misconceptions of linguistics as a narrow or purely theoretical field. The study also presents successful case studies—ranging from post-genocide reconciliation in Rwanda to ecological knowledge preservation in Amazonian communities and strategies to counter digital misinformation—that highlight the transformative potential of applied linguistics when substantively integrated. These examples underscore how linguistics contributes uniquely to framing narratives, decoding ideologies, and designing culturally grounded solutions. The article concludes by calling for a reimagining of interdisciplinary collaboration that positions linguistics as central—not peripheral—in knowledge production and policy formation. Ultimately, it argues that the integration of linguistic perspectives is essential for building more ethical, inclusive, and sustainable civilizational futures.